Estimating frame score from hip height and age - R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1985)
Frame score is a convenient way of describing the skeletal size of cattle. With adequate height growth curves most animals should maintain the same frame score throughout their life, while their actual height increases with age. Environmental factors can alter the normal skeletal growth rate. Nutrition level is a major factor. Cattle fed less than adequate nutrition will growth slower than the tables indicate, while cattle fed extremely high levels will growth faster. Large framed cattle grow faster and for a longer time than small framed cattle. Bulls grow faster than heifers. The accompanying tables and equations are currently the best estimates of cattle height growth rate and have been accepted be the Beef Improvement Federation.
Keywords: Cattlemen& #x27; s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Frame score; Hip height; Age